THE IMPORTANCE OF ENGLISH IN MAINTAINING INTERNATIONAL RELATIONS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The primary language of international relations and diplomacy is English. The representatives of international bodies communicate in the English language. It is vital to establish English as the official language for international organizations in facilitating more efficient collaboration internationally. English dominance in international communication becomes increasingly apparent. This study aimed at gaining a more in - depth understanding of the significance of the English language. This research explores the intersection of English Language and public diplomacy, focusing on how the global spread of English functions as a tool of soft power in international relations. In the 21st century, language is no longer merely a communication medium; it has become a strategic asset for nations seeking to influence global opinion, build international partnerships, and promote cultural values.